THE NATURE OF SOCIETY AND ITS RELATION TO EDUCATION - Alfun Sandi; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
Public relations and education are highly correlated, advanced societies because advanced education and education will only be found in developed societies. The community must actively establish the principles of education that are contained in the philosophy of public education (nation and state). Society is an embodiment of life with humans. In society, the process of social life takes place. In society as an institution of human life, the whole process of life development takes place. Thus, the community can be interpreted as a container or field where the interaction of the community members takes place. But society can also be interpreted as a subject, namely as the embodiment of citizens with all the characteristics in a particular symptom and manifestation or as a whole, socio-psychologically.